The Impacts of Global Research and International Educational Experiences on Texas A&M University System LSAMP Participants - Preuss, Michael; Merriweather, Samuel; Avila, John; Butler-Purry, Karen; Watson, Karan; Walton, Shannon; Obiomon, Pamela; Pezold, Frank; Murry, Jasmine; Roth, Michele; Kelley, Judy; Lamm, Harriet; et al. (Frontiers in Education, 2021)
The Texas A&M University System was one of the first six Louis Stokes Alliance for Minority Participation (LSAMP) awardees. All current members of the Alliance are part of the Texas A&M University System. Many high impact practices (HIP) have been emphasized in the Alliance’s 30 years of programming with Diversity/Global Learning as a focus in the last 14 years. Diversity/Global Learning has been supported in two formats on the Alliance campuses, through traditional study abroad programming and a College of Engineering initiative. Data presented were derived from a number of sources, project evaluation information regarding student perspectives and outcomes, survey research conducted by an independent party, and institutional data and online platforms accessed to assess student outcomes. Triangulation was completed between data sets. Results indicate both forms of programming were efficacious for underrepresented and first-generation students. Outcomes reported were substantial increases in awareness of and interest in graduate school, increases in cultural learning, confidence in travel outside the United States, learning relevant to major, commitment to continuing involvement with research, interest in another similar experience, and willingness to consider employment outside the U.S. Participants reported statistically significant growth in personal, professional, and research skills. They persisted, participated in additional study abroad experiences, and graduated at higher rates than their institutional peers with approximately 90% of informants indicating intention to consider graduate school in the future, over 40% indicating intent to attend immediately following undergraduate study, and 39.4% of 2007–2014 participants enrolling in graduate school by the spring of 2021. Programming described is replicable at and likely to be efficacious for a wide variety of institutions of higher education.